2014
DOI: 10.1074/jbc.m114.589077
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Binding of Plasminogen to Streptokinase in a Catalytic Complex Reveals a Three-step Mechanism

Abstract: Background:We previously showed that plasmin binding to streptokinase is a three-step mechanism with a slow off-rate. Results: Using rapid kinetics and equilibrium binding, we defined the unknown mechanism of plasminogen binding to streptokinase. Conclusion: Encounter complex formation and conformational tightening are weakened in the three-step binding mechanism. Significance: The results define the molecular basis for plasminogen displacement by plasmin in complexes with streptokinase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Degradation of the fibrin clot is catalyzed by fibrinolytic enzymes after the conversion of the zymogen, plasminogen to its active plasmin. A series of fibrinolytic agents such as tissue-type plasminogen activator (tPA, a serine protease) (Collen and Lijnen, 2004), urokinase-type plasminogen activator (uPA, a serine protease) (Duffy, 2002), and bacterial plasminogen activator such as streptokinase (Verhamme and Bock, 2014), have been reported to activate plasminogen to plasmin. Thrombolytic therapy with plasminogen activators are widely used, however they are reported to suffer from low fibrin specificity, undesired side effects such as internal haemorrhage and are also expensive (Erdur et al, 2014;Flemmig and Melzig, 2012;Yong et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of the fibrin clot is catalyzed by fibrinolytic enzymes after the conversion of the zymogen, plasminogen to its active plasmin. A series of fibrinolytic agents such as tissue-type plasminogen activator (tPA, a serine protease) (Collen and Lijnen, 2004), urokinase-type plasminogen activator (uPA, a serine protease) (Duffy, 2002), and bacterial plasminogen activator such as streptokinase (Verhamme and Bock, 2014), have been reported to activate plasminogen to plasmin. Thrombolytic therapy with plasminogen activators are widely used, however they are reported to suffer from low fibrin specificity, undesired side effects such as internal haemorrhage and are also expensive (Erdur et al, 2014;Flemmig and Melzig, 2012;Yong et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic analysis of mini‐Pg activation by SKΔK414 indicated no difference in affinity between native SK and the mutant binding to this Pg form, lacking kringles 1–4, which suggests that Lys 414 may interact with K4 . Stopped‐flow fluorescence binding of SK to active site‐labeled Pg and Pm demonstrated that Lys 414 binding to a Pg/Pm kringle, likely K4, enhances formation of an initial rapid equilibrium encounter complex, succeeded by two sequential conformational changes . The weaker encounter complex affinity, and the faster off‐rates for the second conformational step of SK•Pg* formation compared to SK•Pm, result in a lower affinity of the SK•Pg* complex, and expression of a weaker ‘pro’‐exosite for binding of Pg in the substrate mode.…”
Section: Different Interactions Of Sk With Pg/pm In the Catalytic Andmentioning
confidence: 99%
“…Studies with the deletion mutant SKDK414 showed that the C-terminal Lys 414 residue of SK interacts with an LBS on a Pg/Pm kringle domain, which causes enhancement of the affinity of SK•Pg* and SK•Pm catalytic complex formation [31]. Binding of native SK and SKDK414 to [Glu]Pg was LBS-independent, due to shielding of critical LBS in the compact a-conformation of [Glu]Pg [9,10] binding to a Pg/Pm kringle, likely K4, enhances formation of an initial rapid equilibrium encounter complex, succeeded by two sequential conformational changes [12,26]. The weaker encounter complex affinity, and the faster off-rates for the second conformational step of SK•Pg* formation compared to SK•Pm, result in a lower affinity of the SK•Pg* complex, and expression of a weaker 'pro'-exosite for binding of Pg in the substrate mode.…”
Section: Proteolytic and Cofactor-induced Activation Mechanismsmentioning
confidence: 99%
“…The lysine analogs also block conformational plasminogen activation by the bacterial non-enzymatic cofactor streptokinase (SK), a fibrinolytic that has been displaced by tPA in the US but is still used in many European and non-Western countries. SK has a C-terminal lysine residue that binds to plasmin(ogen) kringles, thereby increasing the affinity of the plasmin(ogen) complexes with SK and the rate of plasminogen activation [114116]. …”
Section: Proteases and Diseasementioning
confidence: 99%